2021
DOI: 10.1038/s41598-021-96333-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bouts of high-intensity interval exercise reverse age-related functional connectivity disruptions without affecting motor learning in older adults

Abstract: Exercise has emerged as an intervention that may mitigate age-related resting state functional connectivity and sensorimotor decline. Here, 42 healthy older adults rested or completed 3 sets of high-intensity interval exercise for a total of 23 min, then immediately practiced an implicit motor task with their non-dominant hand across five separate sessions. Participants completed resting state functional MRI before the first and after the fifth day of practice; they also returned 24-h and 35-days later to asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 94 publications
0
24
4
1
Order By: Relevance
“…Evidence from fMRI studies on physical activity demonstrated the changes in the activity of and functional connectivity between these network hub regions including the hippocampus, parahippocampus, dorsal anterior cingulate cortex (dACC), and ventromedial prefrontal cortex (vmPFC) that primarily subserve executive functions such as working memory, attention, and inhibition [ 15 19 ]. At the more system level, a 12-month aerobic walking intervention was found to increase resting-state functional connectivity between subnetworks of DMN, and between subnetworks of SN [ 20 ], whereas connectivity in the CEN was found to increase after multiple sessions of high-intensity interval training [ 21 ]. Interestingly, the intensity of physical exercise appeared to modulate functional connectivity changes in the hub regions of the CEN [ 22 ], as well as in the DMN subsystems acutely and after 3 months of training [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from fMRI studies on physical activity demonstrated the changes in the activity of and functional connectivity between these network hub regions including the hippocampus, parahippocampus, dorsal anterior cingulate cortex (dACC), and ventromedial prefrontal cortex (vmPFC) that primarily subserve executive functions such as working memory, attention, and inhibition [ 15 19 ]. At the more system level, a 12-month aerobic walking intervention was found to increase resting-state functional connectivity between subnetworks of DMN, and between subnetworks of SN [ 20 ], whereas connectivity in the CEN was found to increase after multiple sessions of high-intensity interval training [ 21 ]. Interestingly, the intensity of physical exercise appeared to modulate functional connectivity changes in the hub regions of the CEN [ 22 ], as well as in the DMN subsystems acutely and after 3 months of training [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data in this manuscript come from a large study on the impact of exercise on behaviour, brain function, and physiology in individuals with stroke. The data reported here are a subset of the larger study (Greeley et al ., 2021, 2023; Neva et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The serial targeting task was employed as the motor training task (Brodie et al ., 2014; Mang et al ., 2016; Greeley et al ., 2021). Participants used their paretic arm to control a frictionless manipulandum to move a cursor between a start position and an end target projected by the Kinarm end-point robot (Kinarm, Kingston, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fMRI studies of physical activity have reported changes in activity of and functional connectivity between brain areas including hippocampus, parahippocampus, dorsal anterior cingulate cortex, and ventromedial prefrontal cortex that primarily subserve executive functions such as memory, attention, and inhibition 2832 . At the network level, a 12-month aerobic walking intervention was found to increase resting-state functional connectivity between DMN nodes 33 , whereas connectivity in the CEN was found to increase after multiple sessions of high intensity interval training 34 . Interestingly, the intensity of physical exercise appeared to modulate functional connectivity changes in the hub regions of the CEN 35 , as well as in the DMN subsystems acutely and after 3 months of training 36 .…”
Section: Introductionmentioning
confidence: 94%